(untitled) (Islamic Sciences Journal, 2023)
ABSTRACT This research indicates that there are people who promoting themselves by issuing direct fatwa in the media without specialization and who are not afraid of the consequences of that. In this research, the importance of the direct opinion and its importance in the media have been clarified, as it has positive and negative aspects, and has explained the most important reasons for the negative aspects and how to deal with them through the duties of states, governments and official bodies in each country. As well as the statement of controls related to the Fatwa program and its management and controls statement for Mufti and the respondent. As well as I explained the causes behind the negative aseects of the direct fatwa in the media، by none participation of enlightened scholars and specialists, or the cancellation of these programs. Rather, they are remedied by correcting the mistakes and negatives in the direct fatwa, for which there is nothing but pros and cons.